THE EFFECT OF TALKING STICK STRATEGY ON STUDENTS’ SPEAKING ABILITY OF ASKING AND GIVING OPINIONS - Gerard (CV. Mitkom Indotama, 2025)
This study aims to examine the effect of the Talking Stick strategy on students' speaking ability, specifically in the areas of asking and giving opinions. The research was conducted with a group of students, focusing on their ability to express themselves in spoken English in an academic setting. The Talking Stick strategy, which involves using a physical object (the